Association of trisomy 21 with anorectal malformation: a cytogenetic study - Mishra, Dewanshi; Sehgal, Garima; Verma, Rakesh K.; Rani, Archana (International Journal of Research in Medical Sciences, 2020)
Background: Anorectal malformations (ARM) are congenital malformations of digestive system resulting from the disturbed development of hindgut during embryogenesis. ARMs involve both sexes; can occur either isolated or in association with other congenital abnormalities and may be associated with chromosomal abnormalities. Association of trisomy 21 with anorectal malformation is well documented. Present study was conducted to assess prevalence of association of trisomy 21 in patients with anorectal malformation. Methods: Total 48 children with diagnosis of anorectal malformation, who were admitted in Department of Paediatric Surgery, King George’s Medical University, Lucknow, Uttar Pradesh, were selected for the study. Blood samples were collected and their cytogenetic analysis was carried out in the Cytogenetics laboratory, Department of Anatomy, KGMU-U.P, Lucknow, India. Results: Among the 48 study subjects, karyogram could be successfully obtained for 45 cases (93.75%). Numerical anomalies were observed in 8.9% cases. Trisomy 21 was found in 6.7%. The prevalence of trisomy 21 was found to more in males (4.5%) as compared to females (2.2%). Prevalence was highest in birth order 3(20%), followed by birth order 2(7.14%) and lowest in birth order 1(3.85%). Trisomy in association with ARM; was observed in children born to females aged >30 years. It was found unrelated to the history of consanguinity. Conclusions: Prevalence of association of trisomy 21 with ARM was found to be 6.7%. This coexistence emphasizes the need for a thorough investigation of patients with ARM.